State rescaling, policy experimentation and path dependency in post-Mao China: a dynamic analytical framework - Lim, Kean Fan (Taylor and Francis, 2017)
This paper evaluates the applicability of the state rescaling framework for framing politico-economic evolution in China. It then presents an analytical framework that examines institutional change as driven by the dynamic entwinement of state rescaling, place-specific policy experimentation and institutional path dependency. The framework problematizes simple ‘transition’ models that portray a mechanistic ‘upward’ or ‘downward’ reconfiguration of regulatory relations after market-like rule was instituted in 1978. It emphasizes, instead, a more established pattern of development marked simultaneously by geographically distinct (and enduring) institutional forms and experimental (and capricious) attempts to transcend them.